PENGARUH PEMASARAN RELASIONAL DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN PADA HOTEL KUBRA KENDARI - NINGSIH, MARLENI SURIA (Business UHO: Jurnal Administrasi Bisnis, 2016)
Thus in this study the number of samples used as many as 43 people. The method of data analysis used is multiple regression analysis.TheÂ results showed the effect of relational marketing positive and significand effect on costomer loyalty. Quality of service and significant positive effect on customer loyalty. Furthemore, relationship marketing and service quality simultaneously positive and significant effect on cutomer loyalty. Keywords : Relational Marketing, Service Quality and Customer Loyalty.